Improvement of Self-Care Behavior of Type II Diabetes Mellitus Patients Using the Diabetes Self Management Education (DSME) Method: Peningkatan Perilaku Perawatan Mandiri Penderita Diabetes Melitus Tipe II Dengan Metode Diabetes Self Management Education (DSME) - Dodik Hartono; Nafolion Nur Rahmat; Erna Handayani (Journal of Nursing Care and Biomolecular, 2023)
Type II of diabetes melitus is the abnormality of glucose metabolisme insulin seretion interference which can cause some cronic complication. (DSME) can facilitate skill knowledge to do self care preventing diabetic ulkus. This research purposes to know self-care behavior of type II diabetes mellitus sufferers using the diabetes self management education (DSME) method at Klinik Holistic Nursing Therapy Probolinggo. This research is pre experimental with design of one group pre-post design. The population is 35 respondents and sample reseach inclusion criteria, is chosen by accidental sampling. The instrument used is independenly care behavior questionnaire of (SSDCA). Then data is collected by editting process, coding, scoring, and tabulating. The data is analized by wilcoxon signed rank test. The results of the study before being given (DSME) showed that the results of self-care behavior from 21 respondents. After being given (DSME), is 12 respondents are sufficient (37.5%). The results of the analysis test showed that there was an effect of (DSME) toward self-care behavior in patients with type II diabetes mellitus with -value = 0.002 <α = 0.05. (DSME) is a program that can be applied to people with type II diabetes mellitus, nurses are expected to use DSME as a health promotion program.   Keywords: Type II Diabetes Mellitus, Self-Care Behavior (DSME)